Application of Maxillomandibular Fixation for Management of Traumatic Macroglossia: A Case Report. Issue 4 (December 2015) - Shanti, Rabie M.; Braidy, Hani F.; Ziccardi, Vincent B.
We present a case of a 14-year-old adolescent boy who has oral cavity after gunshot wound to the tongue presenting with hemorrhage from the tongue requiring coil embolization of the right lingual artery. The patient subsequently developed macroglossia, which was managed with maxillomandibular fixation for a period of 3 weeks with complete resolution of glossal edema.